Social intelligence in health professions educationists: how it helps to deal with challenges at the workplace? a mixed-method study - Laila Shakeel Abbasi; Rahila Yasmeen; Shabana Ali (Journal of the Pakistan Medical Association)
Objective: To identify the social intelligence of medical educationists, and the coping strategies used to deal with workplace challenges.